تأثير النشاط الإشعاعي على عزم رباعي الأقطاب الكهربي الذاتي للنوى الزوجية-الزوجية لسلسلتي اضمحلال الثوريوم واليورانيوم -راديوم (Faculty of Education Scientific Journal, 2025)
The purpose of the current work is to study the relationship between the intrinsic quadrupole moment and the radioactivity of the even-even nuclei of the decay series of thorium and uranium - radium. To achieve our purpose, the intrinsic quadrupole moment  and eccentricity  were calculated and the behavior of the radioactive chain was compared with the change of  and as an indicator of the change in the shape of the nucleus with radioactivity. The value of the intrinsic quadrupole moment was obtained from the value dependent on the quadrupole electric transition probability   which determines the transition from the ground spin state  to the first excited spin state. While the deviation  was calculated from the values of the major  and minor  axes. From our results, it is clear that the radiating nuclei with their decay for both series are trying to achieve more stability by changing their shape from prolate rotation shape towards the ideal spherical shape as a result of changing their self-intrinsic electric quadrupole moment and the eccentricity.
Keywords: radioactivity; eccentricity; Nuclear Dformation; intrinsic quadrupole moment